The main character : a novel - Goldis, Jaclyn (Emily Bestler Books/Atria, 2024)
When reclusive, mysterious author Ginerva Ex takes her on a lavish trip on the newly renovated Orient Express, for helping craft her latest thriller, Rory discovers Ginerva has masterminded the ultimate real-life twisty plot with Rory as her main character, and as lies, deceptions and betrayals pile up, so do the bodies.